Infections Revealing Complement Deficiency in Adults: A French Nationwide Study Enrolling 41 Patients. Issue 19 (May 2016) - Audemard-Verger, A.; Descloux, E.; Ponard, D.; Deroux, A.; Fantin, B.; Fieschi, C.; John, M.; Bouldouyre, A.; Karkowsi, L.; Moulis, G.; Auvinet, H.; Valla, F.; et al.
Abstract : Abstract: Complement system is a part of innate immunity, its main function is to protect human from bacterial infection. As genetic disorders, complement deficiencies are often diagnosed in pediatric population. However, complement deficiencies can also be revealed in adults but have been poorly investigated. Herein, we describe a case series of infections revealing complement deficiency in adults to study clinical spectrum and management of complement deficiencies. A nationwide retrospective study was conducted in French university and general hospitals in departments of internal medicine, infectious diseases enrolling patients older than 15 years old who had presented at least one infection leading to a complement deficiency diagnosis. Forty-one patients included between 2002 and 2015 in 19 different departments were enrolled in this study. The male-to-female ratio was 1.3 and the mean age at diagnosis was 28 ± 14 (15–67) years. The main clinical feature was Neisseria meningitidis meningitis 75% (n = 31/41) often involving rare serotype: Y (n = 9) and W 135 (n = 7). The main complement deficiency observed was the common final pathway deficiency 83% (n = 34/41). Half of the cohort displayed severe sepsis or septic shock at diagnosis (n = 22/41) but no patient died. No patient had family history of complement deficiency. The mean follow-up was 1.15 ± 1.95 (0.1–10) years. Half of the patients had already suffered from at least one infection before diagnosis of complement deficiency: meningitis (n = 13), pneumonia (n = 4), fulminans purpura (n = 1), or recurrent otitis (n = 1). Near one-third (n = 10/39) had received prophylactic antibiotics (cotrimoxazole or penicillin) after diagnosis of complement deficiency. The vaccination coverage rate, at the end of the follow-up, for N meningitidis, Streptococcus pneumonia, and Haemophilius influenzae were, respectively, 90% (n = 33/37), 47% (n = 17/36), and 35% (n = 14/34). This large study emphasizes that complement deficiencies can be revealed in adults by infectious episodes. Most of them were meningococcal infections revealing common final pathway deficiency. To avoid undiagnosis or late diagnosis, adult displaying first episode of N meningitidis infection should be tested for complement deficiency.